The politics of "Unfriending": User filtration in response to political disagreement on social media. (May 2017) - Yang, JungHwan; Barnidge, Matthew; Rojas, Hernando
Abstract: This article examines exposure to political disagreement on social media and user filtration in response to it. Popular arguments suggest that social media sites prevent exposure to political disagreement either through algorithmic filtration or selective affiliation. Another popular argument says that when users are exposed to political disagreement on social media, they filter it from their feeds by "unfriending"/"unfollowing" or "hiding" the author. We put these narratives to the test by examining (a) the relationship between social media use and exposure to political disagreement and (b) the factors that predict user filtration in response to political disagreement. Results from analysis based on a nationally representative sample of Colombian adults in urban areas show that (a) engagement with news and public affairs content on social media is positively associated with exposure to political disagreement and (b) the amount of disagreement users are exposed to is not related to user filtration in response. Highlights: A study of unfriending in response to political disagreement in Colombia. Exposure to political disagreement on social media is related to using social media for news and public affairs content. The amount of political disagreement a social media user encounters is not related to unfriending a contact. Unfriending a contact is predicted by number of friends and time spent on social media platforms.